1995
DOI: 10.1074/jbc.270.24.14292
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Region within the Neuroendocrine Polypeptide 7B2 Responsible for the Inhibition of Prohormone Convertase PC2

Abstract: The highly conserved polypeptide 7B2 and the subtilisin-related prohormone convertases PC1/PC3 and PC2 are broadly distributed in neurons and endocrine cells and are localized to secretory granules. We recently showed that recombinant 7B2 is in vitro a potent inhibitor of PC2 activity, but not of PC1/PC3, and that newly synthesized 7B2 is transiently associated with proPC2 in vivo. In the present study, in vitro mutagenesis was used to identify the region within the 7B2 sequence responsible for the inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 30 publications
3
52
0
Order By: Relevance
“…Several lines of evidence suggest that 7B2 is both an inhibitor and chaperone of PC2 Martens et al, 1994;Benjannet et al, 1995;Zhu and Lindberg, 1995). Inhibition is caused by a C-terminal region of 7B2 that is slowly cleaved by PC2 (van Horssen et al, 1995;Zhu et al, 1996). Interestingly, CPE removes the C-terminal basic residues from the PC2-cleaved 7B2 and eliminates the inhibitory potency of the 7B2 fragment (Zhu et al, 1996); this could partially explain the defective endoprotease processing of prohormones seen in Cpe fat /Cpe fat mice (Naggert et al, 1995;Fricker et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that 7B2 is both an inhibitor and chaperone of PC2 Martens et al, 1994;Benjannet et al, 1995;Zhu and Lindberg, 1995). Inhibition is caused by a C-terminal region of 7B2 that is slowly cleaved by PC2 (van Horssen et al, 1995;Zhu et al, 1996). Interestingly, CPE removes the C-terminal basic residues from the PC2-cleaved 7B2 and eliminates the inhibitory potency of the 7B2 fragment (Zhu et al, 1996); this could partially explain the defective endoprotease processing of prohormones seen in Cpe fat /Cpe fat mice (Naggert et al, 1995;Fricker et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent studies show that 7B2 represents a complex bifunctional binding protein with two domains encoding opposing functions. The N-terminal domain is responsible for the production of activatable pro-PC2 (11, 12) whereas the C-terminal domain (CT peptide) represents a potent PC2 inhibitor (13,14). The mechanism by which the N-terminal domain of 7B2 is able to effect the productive maturation of pro-PC2 to an active enzyme species is not yet clear, but it is thought to involve Golgi-mediated cellular processes rather than a direct effect on activation per se (reviewed in Ref.…”
mentioning
confidence: 99%
“…In addition, both have broad neuroendocrine tissue distributions [24,27,28]. One of the functions of 7B2 is to inhibit PC2 [29,30]. Similar studies showed that proSAAS is a potent and selective inhibitor of PC1 [24,31].…”
Section: Introductionmentioning
confidence: 88%